2011
DOI: 10.1523/jneurosci.6450-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Object Interactions Arises in the Lateral Occipital Cortex Independent of Attentional Modulation from the Intraparietal Sulcus: A Transcranial Magnetic Stimulation Study

Abstract: Our visual experience is generally not of isolated objects, but of scenes, where multiple objects are interacting. Such interactions (e.g., a watering can positioned to pour water toward a plant) have been shown to facilitate object identification compared with when the objects are depicted as not interacting (e.g. To test this hypothesis, we delivered transcranial magnetic stimulation (TMS) to human subjects' LO and IPS while they detected a target object that was or was not interacting with another object to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Similar findings, of enhanced responses in the LOC to interacting objects, have been reported by Kim & Biederman [20]. In addition, Kim et al [21] used the procedure of Green & Hummel [15] (see §2a) while transcranial magnetic stimulation (TMS) was applied to the LOC and to the posterior parietal cortex (PPC), a brain region implicated in the allocation of spatial attention (cf. [22]).…”
Section: Visual and Motor Componentssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar findings, of enhanced responses in the LOC to interacting objects, have been reported by Kim & Biederman [20]. In addition, Kim et al [21] used the procedure of Green & Hummel [15] (see §2a) while transcranial magnetic stimulation (TMS) was applied to the LOC and to the posterior parietal cortex (PPC), a brain region implicated in the allocation of spatial attention (cf. [22]).…”
Section: Visual and Motor Componentssupporting
confidence: 64%
“…First, the results of Roberts & Humphreys [19] show that the differential neural response to pairs of interacting objects is unaffected by whether or not participants attend to the stimuli. Second, the data indicate that interfering with brain activity in the PPC (using TMS) does not disrupt the beneficial effects of interacting objects [21]. Extinction in patients is associated with damage to the PPC [23] and such patients remain sensitive to the effects of action relations between objects [11].…”
Section: Visual and Motor Componentsmentioning
confidence: 93%
“…Previous work that tested for response differences as a function of action relations between objects (e.g., a hammer positioned to hit a nail) provided evidence for greater LO activity to interacting objects than to noninteracting objects (23,24). Patient and transcranial magnetic stimulation studies further showed that action relationships are processed independently of attentional influences from parietal cortex (25,26). Together with the absence of grouping effects in LO in the current study, these previous findings suggest a special status of object grouping based on action relations (26).…”
Section: Discussionmentioning
confidence: 93%
“…Not only is there evidence that average activity in the LOC differentiates between meaningful and meaningless object interactions Roberts & Humphreys, 2010), but also that neural patterns in this region as examined using multi-voxel pattern analysis (MVPA) capture the different types of object scenes (Baeck, Wagemans, & Op de Beeck, 2013). Additional data demonstrate that disrupting LOC's normal functioning by transcranial magnetic stimulation (TMS) abolishes the interaction-based facilitation effect (Kim, Biederman, & Juan, 2011). In summary, these findings suggest that the grouping of objects into a conceptual unit modulates even basic mechanisms of object perception.…”
Section: Introductionmentioning
confidence: 86%